Are Black Phosphorus Hydrogels Antimicrobial Without Photonic Activation? - Leon D. Pope; Shreehari Kodakkat; Aaron Elbourne; Peter C. Sherrell; Nhiem Tran; Kate Fox (Molecules)
Black phosphorus (BP) nanoflakes have attracted interest as an antimicrobial material for wound healing and implant-associated infections due to their bactericidal activity without the use of antibiotics. Hydrogels are frequently used as a delivery system; however, most research uses photonic activation in the form of near-infrared (NIR) laser stimulation to cause rapid BP degradation, reactive oxygen species (ROS) generation, and a localized photothermal effect. For implant-coating applications, using NIR laser stimulation could be challenging in practice, especially for porous orthopedic implants. This article investigates whether BP nanoflakes, suspended in Pluronic F127 (F127) hydrogels, remain effective against Staphylococcus aureus without photonic activation. The experimental results showed 89.4 ± 7.6% bacterial inhibition from BP nanoflakes at a 5120 µg/mL concentration via passive diffusion in F127; however, it could not kill all the bacteria present. It is hypothesized that the F127 gel interface could create a barrier between the bacteria, which continue to multiply in media, and the antimicrobial black phosphorus compound, which degrades in the F127.